Studi Konflik Tanah Objek Reformasi Agraria (TORA) di Desa Sambabo Kecamatan Ulumanda, Kabupaten Majene - Ihsan, Miftahul; Arafat, Andi; Wijayanti, Andi Ridha Yayank (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2022)
Lands for Agrarian Reform is a government policy as one of the Nawacita of President Jokowidodo through the Agrarian Reform program of 9 million hectares through asset legalization schemes and land redistribution of 4.5 million hectares each. Sambabo Village, Ulumanda District, Majene Regency is one of the areas contained in the Indicative Map of Lands for Agrarian Reform Objects. The data collected in this study are Primary Data and Secondary Data. To obtain the necessary data, it is carried out through Library/Document Studies, Interviews and Observations with a total of 30 respondents, using qualitative descriptive analysis. The results of the conflict study investigation show that the implementation of the Land Object for Agrarian Reform is still not in accordance with what the community expects, the proposed release request and those contained in the indicative map are still very far from what the community expects. what the community expects. The lack of socialization and communication carried out by the government resulted in different perceptions by the community and the government itself. The implementation of the Land Objects for the Agrarian Reform must attend to what the community proposes, things that are basic needs to achieve what is aspired to